Synthesis of Analcime Zeolite Using Al and Si from Waste Resources for the Removal of Pb/Cd Ions from Aqueous Solution - Yubin Kang; Byoungyong Im; Jin-Ju Choi; Jin-Ho Yoon; Dae-Guen Kim (Archives of Metallurgy and Materials, 2022)
Zeolites, minerals with the formula Mx/n[AlO2]x(SiO2)y] zH2O, are environmentally friendly materials used as water treatment adsorbents, gas adsorbents, and petrochemical catalysts. This study used a mixture of aluminum black dross and waste glass to synthesize zeolites via a hydrothermal synthesis and analyzed the effects of varying reaction time on phase changes under different synthesis conditions. With increased reaction times, a phase change from zeolite Na-P1 to analcime was observed; on employing hydrothermal synthesis at 150°C for 96 h, the majority of the crystalline structures changed into analcime. Heavy metal cation adsorption was tested to assess the applicability of the synthesized analcime to water treatment. Zeolite adsorption of at least 95% was observed for both Pd and Cd ions. Although a higher level of adsorption was observed for Pb ion than Cd ion, Cd ion was demonstrated to undergo relatively faster adsorption when tested under optimal pulp density at the same level of adsorption (95%).